2D Materials: Single Atomically Sharp Lateral Monolayer p‐n Heterojunction Solar Cells with Extraordinarily High Power Conversion Efficiency (Adv. Mater. 32/2017). Issue 32 (August 2017) - Tsai, Meng‐Lin; Li, Ming‐Yang; Retamal, José Ramón Durán; Lam, Kai‐Tak; Lin, Yung‐Chang; Suenaga, Kazu; Chen, Lih‐Juann; Liang, Gengchiau; Li, Lain‐Jong; He, Jr‐Hau
Abstract : An alloy‐free 2D monolayer WSe2 ‐MoS2 lateral p‐n heterojunction solar cell is demonstrated to exhibit an extraordinary power conversion efficiency of 2.56%, with excellent omnidirectional light harvesting behavior, by Lih‐Juann Chen, Jr‐Hau He and co‐workers in article number1701168 . Temperature‐dependent characteristics are analyzed and the electrode spacing is optimized to achieve gate‐tuning controllability and environmentindependent cell properties.